Spontaneous Regression and Recurrence of a Tumefactive Perivascular Space. Issue 2 (April 2014) - Muttikkal, Thomas Jose Eluvathingal; Raghavan, Prashant
Perivascular spaces can occasionally appear mass-like (tumefactive or giant perivascular space), and can be associated with clinical symptoms. Spontaneous regression of a tumefactive perivascular space is a very rare phenomenon with only two reported cases in the English medical literature. Spontaneous regression of a tumefactive perivascular space along with resolution of clinical symptoms, followed by spontaneous recurrence associated with symptom recurrence is an extremely rare occurrence, which to the best of our knowledge, has not been reported in the medical literature. We describe a case of spontaneous regression of a tumefactive perivascular space, three years after its initial detection, followed by spontaneous recurrence after two years.